Evaluating restorative justice circles of support and accountability: can social support overcome structural barriers? - Bohmert, Miriam Northcutt (International journal of offender therapy and comparative criminology, 2018)
In a climate in which stigmatic shaming is increasing for sex offenders as they leave prison, restorative justice practices have emerged as a promising approach to sex offender reentry success and have been shown to reduce recidivism. Criminologists and restorative justice advocates believe that providing ex-offenders with social support that they may not otherwise have is crucial to reducing recidivism. This case study describes the expressive and instrumental social support required and received, and its relationship to key outcomes, by sex offenders who participated in Circles of Support and Accountability (COSAs), a restorative justice, reentry program in Minnesota. In-depth interviews with re-entering sex offenders and program volunteers revealed that 75% of offenders reported weak to moderate levels of social support leaving prison, 70% reported receiving instrumental support in COSAs, and 100% reported receiving expressive support. Findings inform work on social support, structural barriers, and restorative justice programming during sex offender reentry.